2017
DOI: 10.1016/j.forsciint.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychoactive substances, alcohol and illicit drugs, in Spanish drivers: A roadside study in 2015

Abstract: A survey was conducted during 2015 to monitor psychoactive substance use in a sample of drivers in Spanish roads and cities. Traffic police officers recruited drivers at sites carefully chosen to achieve representativeness of the driver population. A brief questionnaire included the date, time, and personal and driving patterns data. Alcohol use was ascertained through ethanol breath test at the roadside and considered positive if concentrations >0.05mg alcohol/L were detected. Four drug classes were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 10 publications
7
21
1
1
Order By: Relevance
“…Special target groups are adult smokers in rural areas of Africa and Eastern Mediterranean (EMCDDA, 2004). The result of the current study is not consistent with a study conducted on public roads in Spain in 2015 which reported that the highest prevalence of positive results for cannabis (15.2%) was found in the younger age group (18-24 years), cannabis were also more frequently observed in urban areas (Domingo-Salvany A et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…Special target groups are adult smokers in rural areas of Africa and Eastern Mediterranean (EMCDDA, 2004). The result of the current study is not consistent with a study conducted on public roads in Spain in 2015 which reported that the highest prevalence of positive results for cannabis (15.2%) was found in the younger age group (18-24 years), cannabis were also more frequently observed in urban areas (Domingo-Salvany A et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…Detailed information about sample planning (considering both geographical and temporal aspects), driving recruitment, data collection and toxicological aspects can be found elsewhere [1], [3], [4]. Data obtained at the roadside with commercial screening instruments in 2015, after weighting, is presented.…”
Section: Methodsmentioning
confidence: 99%
“…Published results from previous editions of surveys conducted in Spain in 2008 and 2013 following the methodology set up in the framework of the European Union DRUID project (Driving Under the Influence of Drugs) [2] were weighted for traffic intensity. In the 2015 edition traffic intensity was measured in a slightly different way than previous ones and the results were published without weighting [1].…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Salvany et al, 2017; Zeferino et al, 2017).Deve-se ressaltar que todos os casos incluídos neste estudo foram considerados como sendo vítimas do evento lesivo por falta de informações adicionais, porém não se deve ignorar o fato de que aqueles que vieram a ser vítimas também podem ter atuado como agressores em determinadas situações.Além disso, não foram obtidas amostras dos agressores que não vieram a óbito.Não foi possível, portanto, fazer a distinção do uso de substâncias psicoativas entre vítimas e agressores, como alguns autores já propuseram(Darke, 2010).…”
unclassified